The invisible architects: evaluating our understanding of planktonic tunicates in the Atlantic - Cardoso, Ályssa Thayna Pedrosa; Silva, Thaynara Raelly da Costa; da Silva, Elton Alex Correa; Díaz, Xiomara Franchesca García; Neumann Leitão, Sigrid (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Appendicularia are planktonic tunicates that construct numerous gelatinous houses each day, being an important source of food and vertical carbon transport in pelagic environments. However, little is known about these organisms in the Atlantic Ocean. This study aimed to provide an overview of the current state of research of the Appendicularia class in the Atlantic southwest. For this work, we reviewed the state of the art on this group based on bibliographic surveys on academic platforms conducted between October and December 2021, resulting in the selection of 83 publications. Of these, only 13.3% corresponded to studies focused on Appendicularia, and the vast majority addressed is zooplankton. A total of 34 species were recorded in the Brazilian ecoregions, Oikopleura dioica, Oikopleura fusiformis, Oikopleura longicauda and Oikopleura rufescens represent 50% of the records. No research group focusing on Appendicularia was found in Brazil, while Argentina has a strong research group for the Southwestern Atlantic. Contrasting, is required a better data management, and enabling future research and the training of researchers focusing on the study of this class.